ØªØ±Ø¬Ù…Ø© Ø´Ø¹Ø± Ø§Ù„Ø¥Ù…Ø§Ù… Ø§Ù„Ø´Ø§ÙØ¹ÙŠ Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø°ÙƒØ§Ø¡ Ø§Ù„Ø§ØµØ·Ù†Ø§Ø¹ÙŠ ChatGPT (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ©) - Mahasin; Rahmi Nur Baiti; Halimah; Ahmad Muradi (UIN ANTASARI, 2026)
Translation across languages is essential for linking cultures and promoting the dissemination of information in the globalization era. Along with this development, artificial intelligence tools such as ChatGPT are increasingly used to support translation activities. This study evaluates the application of ChatGPT in translating Arabic poetry into Indonesian, focusing on a poem by Imam Shafi’i in Diwan Imam Shafi’i. Using a qualitative descriptive framework, the research analyzes the translation subtance produced by ChatGPT. The data consist of the original Arabic poem, its Indonesian translation generated by ChatGPT, and relevant literature on translation studies. The findings show that ChatGPT applies several translation approaches, including word-for-word, literal, and faithful translation. Nevertheless, weaknesses are identified, particularly in preserving Arabic grammatical structures and accurately interpreting contextual meanings. The translations tend to be literal, with limited cultural and contextual adaptation. Despite these limitations, ChatGPT demonstrates potential in assisting cross-language communication effectively.